Tools for telehealth: A correlational analysis of app‐based hearing testing - David Adkins; Anthea Phuong; Jennifer Shinn; Trey Cline; Jordan Hyland; Matthew L. Bush (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objective Telehealth evaluation of hearing is rapidly evolving; however, the lack of consensus on the most accurate remote hearing test application has made hearing evaluation complicated. The objective of this study was to evaluate the correlation between the pure tone audiometry results obtained from app‐based hearing testing programs and a traditional audiogram. Methods A prospective within‐subject and between‐subject study design was used to correlate audiogram results between app‐based hearing programs and a traditional audiogram. All participants completed a traditional audiogram, 1 commercial app‐based test (ShoeBox), 2 consumer app‐based tests (EarTrumpet and Hearing Test and Ear Age Test [HTEAT]), and a Hearing Handicap Inventory screening version (HHI‐S). Testing was conducted in an acoustically controlled environment (traditional) and a quiet room (app‐based hearing tests). Results A total of 39 participants were enrolled in the study (21 with normal hearing and 18 with hearing loss). In patients with normal hearing, only the commercial hearing testing app (ShoeBox) had a statistically significant pure tone average correlation in both ears with traditional audiometry (Right ear—r = 0.7, p = .005, Left ear—r = 0.66, p = .001). Both consumer and commercial apps had statistically significant correlations with both ears in patients with hearing loss (ranging from r = 0.62 to r = 0.9). Regarding accuracy within 10 dB of the pure tone average of the traditional audiogram of all tested ears, the commercial app‐based test was accurate in 94% for all ears (normal and hearing loss), while consumer app‐based tests were between 14% and 36% for all ears. The HHI‐S indicated no hearing impairment in 95% of those with normal hearing and indicated hearing impairment in 89% of those with hearing loss. Conclusion Commercial‐grade app‐based pure tone audiometry demonstrates overall strong correlation and accuracy with traditional audiometry. The HHI‐S assessment remains a valid and useful tool to predict normal hearing and hearing impairment. Level of Evidence 2